Experimental investigation of the fatigue behavior of glass/epoxy composites evaluated by the stiffness degradation and damage accumulation. (March 2019) - Roundi, Walid; El Mahi, Abderrahim; El Gharad, Abdellah; Rebiere, Jean-Luc
The present paper deals with the mechanical behavior of glass/epoxy composite materials under static and cyclic tensile loading. The tested specimens have been made with different stacking sequences ([02 /902 ]s ; [902 /02 ]s ; [03 /90]s ; [903 /0]s ) according to the vacuum infusion procedure. The results of this investigation show the static behavior of the tested laminated composites characterized by the strain to failure, Young's modulus and tensile strength. Wöhler curves corresponding to each stacking sequence were plotted in order to observe the evolution of the maximum stress S max according to the number of cycles. Fatigue Tests were performed under various applied loading levels ( r ), and these values were chosen to evaluate the effect of loading level on the stiffness degradation and damage growth in the tested specimens. Afterward the evolution of the global damage factor ( D) according to the number of cycles was calculated in function of the core characteristics, applied loading level ( r) and type of loading. The cyclic behavior of the composite laminates mainly depends on the progressive developments of damage mechanisms such as matrix cracking, delamination, and fiber breakage.